Anti-inflammatory, Phytoestrogenic And Antioxidative Role Of Labisia Pumila In Prevention Of Postmenopausal Osteoporosis - M. E. Nadia,; A. S. Nazrun; M. Norazlina; N. M. Isa; M. Norliza; S. Ima Nirwana (Hindawi Publishing Corporation, 2024)
Osteoporosis is characterized by skeletal degeneration with low bone mass and destruction of microarchitecture of bone tissue which is attributed to various factors including inflammation. Women are more likely to develop osteoporosis than men due to reduction in estrogen during menopause which leads to decline in bone-formation and increase in bone-resorption activity. Estrogen is able to suppress production of proinflammatory cytokines such as IL-1, IL-6, IL-7, and TNF-α. This is why these cytokines are elevated in postmenopausal women. Studies have shown that estrogen reduction is able to stimulate focal inflammation in bone. Labisia pumila (LP) which is known to exert phytoestrogenic effect can be used as an alternative to ERT which can produce positive effects on bone without causing side effects. LP contains antioxidant as well as exerting antiinflammatory effect which can act as free radical scavenger, thus inhibiting TNF-α production and COX-2 expression which leads to decline in RANKL expression, resulting in reduction in osteoclast activity which consequently reduces bone loss. Hence, it is the phytoestrogenic, anti-inflammatory, and antioxidative properties that make LP an effective agent against osteoporosis.